2017
DOI: 10.1101/pdb.top077610
|View full text |Cite
|
Sign up to set email alerts
|

Chemostat Culture for Yeast Physiology and Experimental Evolution

Abstract: Continuous culture provides many benefits over the classical batch style of growing yeast cells. Steadystate cultures allow for precise control of growth rate and environment. Cultures can be propagated for weeks or months in these controlled environments, which is important for the study of experimental evolution. Despite these advantages, chemostats have not become a highly used system, in large part because of their historical impracticalities, including low throughput, large footprint, systematic complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In addition, while the culture continued to grow over the course of the month, the data became noisy after a period of about two and a half weeks, perhaps because of evolution occurring within the population [12,23]. For example, if a cell that is wild-type at the canavanine locus acquires a mutation that enables it to compete significantly better for nutrients in the chemostat environment, then the number of observed canavanine-resistant colonies will drop below that expected for the given level of mutagen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, while the culture continued to grow over the course of the month, the data became noisy after a period of about two and a half weeks, perhaps because of evolution occurring within the population [12,23]. For example, if a cell that is wild-type at the canavanine locus acquires a mutation that enables it to compete significantly better for nutrients in the chemostat environment, then the number of observed canavanine-resistant colonies will drop below that expected for the given level of mutagen.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous culture systems allow for the long-term, controlled growth of microorganisms or cultured cells. Consequently, they have been used for many scientific and industrial uses, including producing biologics like small molecules [13] and recombinant proteins [4,5]; assessing the growth rate [69] or metabolism [10,11] of microorganisms or cultured cells under defined conditions; and for studying evolution [1214]. Continuous culture systems typically operate in one of two modes: a chemostat, where a limited amount of nutrients are constantly added to the culture, or a turbidostat, where the culture density is kept constant [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong correlation between ESR strength and doubling times in complex aneuploid strains suggested that proliferation rate was the primary determinant of ESR strength. To directly test this possibility, we examined whether equalizing proliferation rate among complex aneuploid strains and euploid control strains affected the correlation between ESR strength and degree of aneuploidy by culturing cells in a phosphate-limited chemostat (4,13). When proliferation rate was equalized in this manner, the ESR gene expression signature was no longer evident in aneuploid strains ( Fig.…”
Section: Proliferation Rate Determines Esr Strengthmentioning
confidence: 99%
“…Continuous culture systems allow for the long-term, controlled growth of microorganisms or cultured cells. Consequently, they have been used for many scientific and industrial uses, including producing biologics like small molecules [1][2][3] and recombinant proteins [4,5]; assessing the growth rate [6][7][8][9] or metabolism [10,11] of microorganisms or cultured cells under defined conditions; and for studying evolution [12][13][14]. Continuous culture systems typically operate in one of two modes: a chemostat, where a limited amount of nutrients are constantly added to the culture, or a turbidostat, where the culture density is kept constant [15].…”
Section: Introductionmentioning
confidence: 99%